2014
DOI: 10.1159/000369818
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A in Diagnosing and Monitoring Patients with Gastroenteropancreatic Neuroendocrine Neoplasms: A Large Series from a Single Institution

Abstract: Background/Aims: Plasma chromogranin A (CgA) is the most widely used biochemical biomarker in the diagnostic workup and follow-up of gastroenteropancreatic neuroendo- crine neoplasms (GEP-NENs). Herein, we assessed the clinical utility of CgA in diagnosing and monitoring a large series of GEP-NENs. Patients and Methods: A total of 181 GEP-NEN patients (87 males, 94 females) with pancreatic (n = 81) and gastrointestinal neoplasms (n = 100) were included; 99 patients had grade (G)1 NENs (Ki-67 ≤2%), 57 G2 NENs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 43 publications
0
48
2
4
Order By: Relevance
“…36,37 CgA has been validated as a prognostic marker in midgut NET in randomized clinical trials. 38 Pancreastatin, a breakdown product of CgA, may be more specific in certain contexts, such as patients using proton pump inhibitors (which raise CgA levels).…”
Section: Resultsmentioning
confidence: 99%
“…36,37 CgA has been validated as a prognostic marker in midgut NET in randomized clinical trials. 38 Pancreastatin, a breakdown product of CgA, may be more specific in certain contexts, such as patients using proton pump inhibitors (which raise CgA levels).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of metrics have been assessed to evaluate the use of these markers. For example, a 30% decrease in CgA (from pretreatment levels) is considered predictive of SSA efficacy [38], while an increase in three consecutive measurements is considered to anticipate relapse after midgut surgery [39]. Some authors proposed that alterations of ≥25% in CgA may have good sensitivities (>75%) and specificities (>85%) for predicting disease events [33] while others suggested that levels twice the ULN (∼300 µg/l or 300 ng/ml) [32] or higher (≥600) [40] are effective predictors of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our data only included the Chinese population, and it is not clear whether the results could be generalized to populations worldwide. Second, additional known risk factors that could predict survival were not evaluated, including histological growth pattern, mitotic rate, Ki-67 index, and immunohistochemistry markers, such as chromogranin A (CgA) and synaptophysin (Syn) [21,[30][31][32][33]. Finally, our analysis did not adjust for treatment approaches that may impact outcomes [34].…”
Section: Discussionmentioning
confidence: 99%